The book of secrets - Voigt, Cynthia (Voigt, Cynthia. Mister Max, 2014)
Self-reliant Max Starling, a twelve-year-old detective and problem solver, struggles to keep his identity a secret as he investigates a case of arson, while cryptic messages from his still missing parents indicate that they need rescuing.